α-glucosidase inhibitors from the leaves and stems of Erythrina Variegata L. collected in Hanoi - Phi-Hung Nguyen; Savanchith Xayavong; Ngoc-Thao-Vy Trinh; Dang Ngoc Quang; Le Thi Phuong Hoa; Thi-Thuy Do; Thi-Ha Vu; Thi-Thuc Bui; Thi-Thu-Ha Trinh (Tạp chí Khoa học và Công nghệ, 2023)
Four secondary metabolites, including daidzein (1), genistein (2), glycitein (3), and daidzin (4) have been isolated and structural elucidated from the methanolic extract of the stems and leaves of Erythrina variegata L. collected in Hanoi city, Vietnam. These compounds showed good in vitro inhibition on α-glucosidase enzyme with IC50 values of 97.6 ± 0.6, 230.4 ± 0.4, 34.3 ± 0.9, and 217.2 ± 0.2 µM, respectively as compared with that of acarbose (IC50 value of 125.8 ± 1.2 µM). This finding suggests the possible application of product containing high content of these compounds from the leaves and stems of E. variegata L. for research and development of anti-obese agent.